Implementation and Educational Outcomes of National Policy Framework on Learners and Schools as Zones of Peace - Tumamin, Datu Lawan M.; Usop, Annierah Maulana; Lumbu-an, Jenevieve D. (Future Science / FSH-PH Publications, 2024)
fforts continue to label each school in the Philippines as a zone of peace. However, instability in regions with ongoing conflicts keeps schools, teachers, students, and staff at risk. The vulnerability in these areas remains a persistent challenge. The National Policy Framework on the Learners and Schools as Zones of Peace (LSZOP) acknowledges this vulnerability, aiming to address the immediate impact of armed conflicts on learners and schools, thereby fostering the establishment of a resilient society. Thus, this study was created to delineate the implementation of the national policy framework on LSZOP and explain its correlation with educational outcomes in Private and Public Secondary Schools in Lambayong, Sultan Kudarat. Employing an explanatory sequential mixed method design, the study enlisted 84 school stakeholders as respondents. A researcher-made questionnaire and semi-structured interview guide were facilitated through stratified random sampling. Quantitative analysis reveals the significant influence of the LSZOP implementation on secondary school development, particularly concerning education for peace, peace for education, and crisis management. Meanwhile, qualitative insights reveal schools' commitment to fairness irrespective of students' tribe, religion, or ethnicity, emphasized by crafted rules promoting cultural sensitivity, fairness, and children's rights. Notably, schools prioritize values formation and respect for individual differences, fostering peace and order within their premises. Nevertheless, findings indicate no significant relationship between the national policy framework implementation and governance as an educational outcome among secondary schools in Lambayong, Sultan Kudarat. The study advocates for reinforcing LSZOP implementation to realize its envisioned objectives.